STUDI BEBERAPA FAKTOR PENDUKUNG PENGEMBANGAN EKOWISATA BERBASIS FAUNA ENDEMIK DI HUTAN SAWINGGRAI KECAMATAN MIOSMANSAR KABUPATEN KEPULAUAN RAJA AMPAT PROPINSI PAPAUA BARAT - Yeblo, Michael; Kiroh, H. J.; Nangoy, M. J.; Rawung, V. R.W. (ZOOTEC, 2015)
THE STUDY OF SUPPORTING FACTORS THE ECOTOURISM DEVELOPMENT OF ENDEMIC FAUNA IN THE FOREST SAWINGGRAI, DISTRICT MIOSMANSAR, RAJA AMPAT, PAPUA BARAT. Ecotourism is nature tourism that focuses on an area or areas of conservation (Protected area) that contribute to the welfare of local communities and conservation and education for the community. Raja Ampat Islands is an area that has the potential to be used as attractions, Sawinggrai Forest is one of the forest that has the potential of ecotourism is good enough to be developed, which is unique in the forest with animals - including endemic animal bag Semar (Nepenthes sp), Resin (Agathis sp), Blue Beetle (Eulophis geoffroyi), Red Bird of Paradise (Paradiseaea Rumbra), and a variety of other animals. This study aims to determine the factors supporting the development of ecotourism endemic fauna in the forest in the village Sawinggrai Kapisawar, Sawinggrai, Yenwapnor, District Miosmansar Raja Ampat. Research on the study of several contributing factors Sawinggrai forest ecotourism development, was held on October 11 until the date of 18 November 2014 took place in the village of Kapisawar, Sawinggrai, Yenwapnor, District Miosmansar Raja Ampat which is located near the forest Sawinggrai. Which is the object of this research is endemic fauna in Raja Ampat. The equipment used in this study is Digital Cameras, ATM (Stationery Writing), a computer to process data, questionnaires in the form of a list of questions related to the community's response to the endemic fauna-based ecotourism development. This study uses a survey and interviews directly with the public. The variables measured were: 1). Level of education, 2). Community work, 3). Flora and fauna endemic, 4). Community response to the development of ecotourism, 5). Public disturbance to fauna endemic step and, 6). Based on the results of the data analysis and discussion for all variables in this study, it can be concluded that some of the factors supporting the development of forest-based ecotourism endemic fauna and forest Sawinggrai good enough Sawinggrai is feasible to be a place of ecotourism. Â  Keywords: ecotourism, endemic fauna, supporting factor, public education